2009
DOI: 10.1007/s00213-009-1537-0
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable effects of noradrenaline, dopamine, and serotonin uptake blockade on stop task performance in rats

Abstract: Rationale The stop-signal paradigm measures the ability to stop a motor response after its execution has been initiated. Impairments in inhibiting inappropriate behavior and prolonged stop-signal reaction times (SSRTs) are characteristic of several psychiatric disorders, most notably attention deficit/hyperactivity disorder. While there is relative consensus regarding the anatomical substrates of behavioral inhibition, the neurochemical imbalance responsible for the deficits in stopping displayed by impulsive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
135
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(150 citation statements)
references
References 69 publications
12
135
2
1
Order By: Relevance
“…Our data were consistent with findings in people and previous rat models (Aron et al, 2003;Bari et al, 2009;Bari et al, 2011;Broos et al, 2012;Chamberlain et al, 2006;Eagle et al, 2007;Tannock et al, 1989) and showed that the general ability of these drugs to enhance stopping in the SSRTT extended to mice. The effects of both drugs were dose dependent with the inhibition-promoting effects being lost at higher doses, presumably as a result of a relative reduction in pharmacological selectivity.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data were consistent with findings in people and previous rat models (Aron et al, 2003;Bari et al, 2009;Bari et al, 2011;Broos et al, 2012;Chamberlain et al, 2006;Eagle et al, 2007;Tannock et al, 1989) and showed that the general ability of these drugs to enhance stopping in the SSRTT extended to mice. The effects of both drugs were dose dependent with the inhibition-promoting effects being lost at higher doses, presumably as a result of a relative reduction in pharmacological selectivity.…”
Section: Discussionsupporting
confidence: 93%
“…To enable crossspecies comparisons, we used the same dose ranges used in previous SSRTT studies in rats (Bari et al, 2009;Eagle et al, 2007). These doses ranges have been shown to be effective in other behavioral tasks in mice (Davis and Gould, 2007;Griffin et al, 2013) and lead to systematic changes in monoamine release in mouse mPFC assessed using microdialysis (Koda et al, 2010).…”
Section: The Clinically Effective Drugs Methylphenidate and Atomoxetimentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, this work points to mPFC as a critical player during response inhibition and suggests that reduced prefrontal activation/function in disorders such as ADHD drive behavioral impairments (Euston et al, 2012). Consistent with this hypothesis, patients diagnosed with ADHD have been successfully treated with the noradrenaline and dopamine (eg, methylphenidate and atomoxetine) reuptake inhibitors (Aron et al, 2003;Bari et al, 2009;Bedard et al, 2003;DeVito et al, 2009;Robinson et al, 2008;Tannock et al, 1989) that have been shown to impact prefrontal cortex in both humans and rats. For instance, in humans, atomoxetine administration increases inferior frontal activity in human participants (Chamberlain et al, 2009) and methylphenidate reverses ADHD-associated hypofrontality (Vaidya et al, 1998).…”
Section: Discussionmentioning
confidence: 70%
“…Thus, studies in rats and humans have shown that manipulating 5-HT does not affect performance on tasks of inhibition that have no clear affective component, such as the stop-signal reaction-time task Cools et al, 2005;Chamberlain et al, 2006;Bari et al, 2009;Eagle et al, 2009), the self-ordered spatial working memory task (Walker et al, 2009), and the go-nogo task (Rubia et al, 2005;Evers et al, 2006) (but see LeMarquand et al, 1999).…”
Section: The Coupling Between Inhibitory and Aversive Effects Of Seromentioning
confidence: 99%